(untitled) (Lex localis - Journal of Local Self-Government, 2020)
The role of women in society every day is growing. Women achieve significant business outcomes, along with men, although their efforts are often not evaluated in the same way. Despite their extraordinary commitment to the jobs they perform, women still find themselves in the so-called "glass ceiling" - barriers that prevent them from progressing to better careers and to be equally valued and paid as men. Nowadays, there is a great desire and engagement of all layers of society and the state to change that situation so that women can prove their abilities in the most responsible positions, both in companies and public sectors as well. This paper starts from the fact that there is no favoring of men in relation to women in management positions in the state administration in Serbia, and that the main preconditions for someone to perform these functions are knowledge, education and work experience.